Premier festival de Musique Electronique. - Plan K, Brussel (Brussel : Omegalfa asbl, 1980)
Bekaert, Jacques ; Beyls, Peter ; Blondia, Rudi ; Daleth Synthesizer Quartet ; De Smet, Raoul ; Goethals, Lucien ; Goeyvaerts, Karel ; Keev, Gilles ; Küpper, Leo ; Michel, P.B. ; Nuyts, Frank ; Pierre, Alain ; Pousseur, Henri ; etc.
Premier festival de Musique Electronique, Plan K, Brussel, 10 & 11 octobre '80 de 15h à minuit
boek